Description of two unknown females of Epeus Peckham & Peckham from China (Araneae: Salticidae) - Meng, Xiang-Wei; Zhang, Zhi-Sheng; Shi, Ai-Ming (Zootaxa, 2015)
The jumping spider genus Epeus Peckham & Peckham presently includes 15 species, mainly from South and Southeast Asia (World Spider Catalog 2015). Species of this genus have the cymbium of male palp flattened and elongated, with a basal apophysis retrolaterally, pointing postero-ventrally; tegulum with a tongue-like process; filiform embolus; and epigyne with long copulatory ducts with several loops.